Essentials of ADHD assessment for children and adolescents - Sparrow, Elizabeth P. (Essentials of psychological assessment, 2014)
"This indispensable resource provides step-by-step guidelines for conducting a thorough, responsible evaluation for ADHD in children and adolescents. Focusing on the pragmatic needs of the practicing clinician, the authors address not only the broad concepts integral to conducting sound ADHD assessments but also the specifics that will enable practitioners to implement those principles. This essential guide is appropriate for seasoned clinicians who wish to add ADHD evaluations to their practices, as well as new clinicians and graduate students who are developing expertise. "--